(3TQM GdeUGOQI GdeTghQI dcJGH GdCUhd (B[ (3dCbdjOS(B] (3eY PcQ GdHQGgjf GdJi CbjeJ YdjgGs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GbdjOSs
(3ChdgG (B:s
(3Cbhd HYO MeO Gddg ejSQ cd YSjQ s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B924 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(2760) s
Keywords: (3GdQjGVjGJs